Gender, Sexuality, and Religion - Nesbitt, Paula (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This seminar will explore of gender the relationship, sexuality, and religion by examining how they interplay across diverse historical, contemporary, and cross-cultural contexts. Part One of the seminar will focus on theoretical issues such as gender and sexuality construction, social identity, authority, and social control, and how these are lived out through various religious perspectives and communities. The second part of the seminar, building on these theoretical foundations, will focus on comparing similarities and differences of gender and sexuality-related issues and movements for social change across specific religious traditions and cultures. Part Three of the seminar will focus primarily on the United States as we study women and ordained religious leadership, alternative feminist religious movements, and the development of social policy and activism. Parts Two and Three should provide an intriguing comparison of how women address inequality across different social, ideological, and role structures, and how these relate to more deeply-rooted issues of human sexuality.